'LEGITIMATE RAPE', MORAL COHERENCE, AND DEGREES OF SEXUAL HARM. Issue 41 (14th September 2015) - Earp, Brian D.
Abstract : In 2012, the politician Todd Akin caused a firestorm by suggesting, in the context of an argument about the moral permissibility of abortion, that some forms of rape were 'legitimate' (i.e., carried out with great force or violence). This seemed to imply that other forms of rape must not be legitimate (i.e., carried out with less force or violence). In response, several commentators pointed out that rape is a 'heinous crime' and that there are 'no varying degrees of rape'. While the intention of these commentators was clear, I argue that they may – inadvertently – have played into the very stereotype of rape (implicitly) endorsed by Akin. Such a response, I claim, actually obscures a range of sexual harms, including some that may not rise to the level of being a crime. I also offer some thoughts on the moral psychology behind anti-abortion arguments of the kind advanced by Akin.